Hristos și hristologie în operele eshatologice ale lui Hipolit - Iosif Diaconu (TheoRhēma, 2020)
At the beginning of the third century of the Christian era, Hippolytus wrote two treatises on eschatology. In addition to his eschatological position, he expressed several Christological ideas, based on which we can understand the following three aspects of his position on this issue. First, Hippolytus features among the theologians of the Ante-Nicene period. These use the term Logos, taken from the prologue of the Gospel of John, in a Christological sense. Second, Hippolytus distinguishes two phases of Christ’s history. The ﬁrst phase refers to Christ before the incarnation. Referring to the preexistent Christ, Hippolytus calls him Logos. The second phase is after the incarnation, when Christ becomes the Son. So, for Hippolytus, Christ is Son only on account of the incarnation. Third, Hippolytus resolutely declares that the Logos is God and that, by incarnation, He is the Son of God. Hippolytus does not resort to philosophical speculation to explain the Christ mystery. Rather, he remains within Christological parameters oﬀered by the biblical revelation. That is why the Christology of Hippolytus is soteriological or functional and not ontological.